A homologous overexpression system to study roles of drug transporters in Candida glabrata. Issue 4 (3rd June 2020) - Kumari, Sonam; Kumar, Mohit; Khandelwal, Nitesh Kumar; Pandey, Ajay Kumar; Bhakt, Priyanka; Kaur, Rupinder; Prasad, Rajendra; Gaur, Naseem A
Abstract: Considering the relevance of drug transporters belonging to ABC and MFS superfamilies in pathogenic Candida species, there has always been a need to have an overexpression system where these membrane proteins for functional analysis could be expressed in a homologous background. We could address this unmet need by constructing a highly drug-susceptible Candida glabrata strain deleted in seven dominant ABC transporters genes such as CgSNQ2, CgAUS1, CgCDR1, CgPDH1, CgYCF1, CgYBT1 and CgYOR1 and introduced a GOF mutation in transcription factor (TF) CgPDR1 leading to a hyper-activation of CgCDR1 locus. The expression system was validated by overexpressing four GFP tagged ABC ( CgCDR1, CgPDH1, CaCDR1 and ScPDR5 ) and an MFS ( CgFLR1 ) transporters genes facilitated by an engineered expression plasmid to integrate at the CgCDR1 locus. The properly expressed and localized transporters were fully functional, as was revealed by their several-fold increased drug resistance, growth kinetics, localization studies and efflux activities. The present homologous system will facilitate in determining the role of an individual transporter for its substrate specificity, drug efflux, pathogenicity and virulence traits without the interference of other major transporters. Abstract : Development of a strain containing seven ABC transporter deletion with overexpressed CgCDR1 locus and its expression system for characterizing membrane protein in pathogenic yeast Candida glabrata.